The effect of systemic rifampicin treatment on inferior alveolar nerve regeneration in rats following crush injury - Diker, Nurettin; Çağlayan, Berrak; Helvacıoğlu, Fatma; Kılıç, Ertuğrul (Wiley, 2020)
Axonal regeneration of the inferior alveolar nerve (IAN) is a therapeutic target for functional recovery after peripheral nerve injury. Rifampicin exerts anti-apoptotic, anti-inflammatory, and anti-oxidant effects on nerve tissues that may enhance functional recovery after peripheral nerve injury. The aim of the present study was to evaluate the therapeutic effects of systemic rifampicin following IAN crush injury. Following the nerve crush injuries of the IAN, 24 Sprague-Dawley rats were randomly divided into three groups to receive daily intraperitoneal injections of either vehicle, 5 mg kg(-1) rifampicin, or 20 mg kg(-1) rifampicin. Twenty-four days after induction of nerve injuries, Fluorogold (FG) was injected over the mental foramen for the evaluation of neuronal survival. At the end of the four-week period, histologic and histomorphometric examination of IAN samples were performed and FG positive cells were counted in the trigeminal ganglion sections. FG positive cells were significantly more frequent in the 20 and 5 mg kg(-1) rifampicin groups than in the vehicle-treated group. Electron microscopic analyses revealed that the percentage of axons with optimum g-ratio was significantly lower in the vehicle group than in both treatment groups. In conclusion, systemic rifampicin treatment can enhance peripheral nerve regeneration.
Keywords: Mandibular Nerve; Nerve Regeneration; Rifampicin; Trigeminal Ganglion